A New Chuvash–Common Turkic Cognate and its Relation to Tocharian - Orçun Ünal (Orientalia Suecana)
This study proposes a new cognate relationship between Chuvash vĕre- ‘to boil’ and Common Turkic *özä- ‘to suffer’. Both can be traced back to Proto-Turkic *ör₂ǟ- ‘to burn (intransitive), be hot’, derived from *ör₂V-. The semantic shift from ‘to burn’ to figurative meanings such as ‘to grieve’ or ‘to take pains’ is widely attested across languages. The Proto-Turkic form may itself be a loanword from an unattested Proto-Tocharian cognate *u̯ʲər- of Proto-Indo-European *uerh₁- ‘to be hot’. This borrowing provides additional support for the rhotic nature of Proto-Turkic */r₂/. Furthermore, the paper connects Proto-Turkic *ör₂V- to Common Turkic *ört ‘flame’ and Chuvash virt ‘burning, fire’.